Molecular Mechanisms of Neurotransmitter Release - Wang, Zhao-Wen.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2008)
Within the complex neuronal network of the nervous system, neuron-to-neuron communication occurs mainly through chemical synapses, where the presynaptic nerve terminal releases neurotransmitters that control the function of postsynaptic neurons by acting on postsynaptic receptors. Recent decades have brought groundbreaking new developments and a wealth of knowledge to this field. In Molecular Mechanisms of Neurotransmitter Release, leading experts provide concise, up-to-date information on all major molecular mechanisms involved, with complete background information and figures and diagrams to further elucidate key concepts or experiments. Comprehensive and cutting-edge, Molecular Mechanisms of Neurotransmitter Release is sure to provide a learning tool for neuroscience students, a solid reference for neuroscientists, and a source of knowledge for all those who have a general interest in the ever-evolving field of neuroscience.
The Architecture of the Presynaptic Release Site -- Multiple Modes of Fusion and Retrieval at the Calyx of Held Synapse -- Roles of SNARE Proteins in Synaptic Vesicle Fusion -- Roles and Sources of Calcium in Synaptic Exocytosis -- Regulation of Presynaptic Calcium Channels -- Synaptotagmin: Transducing Ca2+-Binding to Vesicle Fusion -- Functional Interactions Among the SNARE Regulators UNC-13, Tomosyn, and UNC-18 -- Roles of the ELKS/CAST Family and SAD Kinase in Neurotransmitter Release -- The Role of Potassium Channels in the Regulation of Neurotransmitter Release -- Modulation of Neurotransmitter Release and Presynaptic Plasticity by Protein Phosphorylation -- Synaptic Vesicle Endocytosis -- Lipids and Secretory Vesicle Exocytosis -- Neurotransmitter Reuptake and Synaptic Vesicle Refilling -- Regulation of Neurotransmitter Release by Presynaptic Receptors -- Transsynaptic Regulation of Presynaptic Release Machinery in Central Synapses by Cell Adhesion Molecules -- Differential Regulation of Small Clear Vesicles and Large Dense-Core Vesicles.
Keywords: Neurosciences; Cell biology; Neurobiology; Neurology .; Human physiology; Neurosciences; Cell Biology; Neurobiology; Neurology; Human Physiology